NUTRIENT CONTROL OF THE GLOBAL OCCURRENCE OF ISOLATED CARBONATE BANKS - Vecsei A. (My University, 2003)
The growth and origin of the world's isolated carbonate banks are as yet not completely understood. This paper presents a comparison of the areas, depths, and latitudinal distribution of the world's carbonate banks. These are then compared with chemical parameters of seawater in the upper mixed zone of the oceans and at depth. The results allow large-scale inferences to be made on the interacting controls on bank growth and distribution. The data support the hypothesis that nutrient-rich waters commonly control bank depth and size.
Keywords: ISOLATED CARBONATE BANKS; GROWTH; DEPTH AND AREA; CONTROLS; NUTRIENTS